The Influence of Managerial Ownership, Company Growth and Profitability on Dividend Policy in LQ45 Companies 2019-2021 - Magdalena Napitupulu, Maria; Hasnawati, Sri; Kufepaksi, Mahatma (FKIP Universitas Lampung, 2024)
Dividend policy is a decision about how much of current earnings will be paid out as dividends rather than retained earnings which will then be reinvested in the company. dividend policy can be measured through the dividend payout ratio (DPR). The ratio shows the percentage of the company's earnings that are paid out to shareholders in cash. Companies that have a high DPR and increase from year to year can provide positive signals to investors, because dividend announcements can be used as information by shareholders regarding company performance. This study aims to determine the effect of managerial ownership, company growth, profitability on dividend policy in LQ45 companies 2019-2021. This research is quantitative research. The data used is also secondary data taken from the official website of the Indonesia Stock Exchange in the form of financial reports of LQ45 companies listed on the IDX. Based on the results of data analysis and discussion of the effect of Managerial Ownership, Company Growth, and Profitability on Dividend Policy in LQ45 companies 2019 - 2021, it can be concluded. The managerial ownership variable has no effect on dividend policy as proxied by the dividend payout ratio. The company growth variable affects the dividend policy proxied by the dividend payout ratio. This indicates that any increase or decrease in total assets during the observation period affects the dividend to be distributed to shareholders. The profitability variable has no effect on dividend policy proxied by the dividend payout ratio.Keywords: Managerial Policy, Company Growth, Profitability, Dividend PolicyDOI: http://dx.doi.org/10.23960/E3J/ v7i1.34-42